Influência dos fatores ambientais na abundância de Portunus spinimanus latreille, 1819 (Crustacea, Brachyura, Portunidae) na região de Ubatuba (SP) - Santos, Sandro (Ciência e Natura, 2000)
This work aimed to study the environmental factors influence on P. spinimanus abundance in the sublittoral sediments of Fortaleza bay, Ubatuba (SP). The collects were made during one year, from November/1988 to October/1989, with a shrimp fishery boat equipped with 2 otter-trawl. Temperature, salinity, depth, dissolved oxygen content, organic material amount of the sediment and its granulometric composition were the environment factors sampled. The procedure adopted here consisted in to distribute the environment factors results in strata, to determine the values frequency and the number of captured individuals in each stratum through the 84 samples. The transformed abundance index was calculated by means the formula A = Ln (x + 1), where, x = mean number of individuals and Ln = neperian logarithm. The abundance index lended 10 increase with the temperature elevation and it was high in 31.6 to 33.2 % of salinity. The abundance index for both dissolved oxygen and organic material contents were characterized by a normal curve. The individuals were abundant in the first two strata of depth. With relation to granulometric fractions, the animals were more abundant in subareas with gravel and very coarse sand than the others. Based on this results and field observations it can be concluded that the presence of P. spinimanus is associated to a group of environment factors among them the sediment texture (gravel and very coarse sand) and to protected sites in the bay, characterized by a relatively calm water.